Vibration cause analysis and elimination of stagnant branch pipeline. (November 2022) - Kun, Cai; Jianrong, Zou; Yilin, Cai; Jie, Qin; Changfan, Zhu; Jian, Qiu; Mingguang, Zheng
Highlights: Fluid acoustic structure coupling vibration is rare in NPP, especially in the stagnant branch of RCL. This phenomenon of fluid acoustic solid coupling vibration of one stagnant branch pipeline are found in HFT of NPP. This paper reports the piping vibration, root cause analysis of vibration, modification and its effect in operation. Abstract: Fluid acoustic structure coupling vibration is rare in nuclear power plant (NPP), especially in the stagnant branch of reactor coolant loop (RCL). This paper reports the phenomenon of fluid acoustic solid coupling vibration of one stagnant branch pipeline founding in the hot function test (HFT) of NPP. Field measurement shows that the vibration exceeds the limit value so it is necessary to determine the root cause of pipeline vibration and provide the modified layout. Based on the data of single point measurement, on-line monitoring, knocking test, acoustic modal calculation and modal analysis, the authors obtain the vibration characteristics and laws of pipelines and infers the acoustic solid coupling. The computational fluid dynamics (CFD) analysis and Strouhal number calculation, the inference of fluid acoustic coupling is identified. According to the above inference, the modified layout and the vibration prediction of the modified layout are proposed. After modification the HFT and the power up test was started. The vibration trend was consistent with the prediction, which verified that the fluid acoustic structure coupling was the root cause of the stagnant branch vibration. The amplitude of the modified the stagnant branch pipeline reduced in the whole process of temperature rise. The operation meets the limit requirements. The stagnant branch can operate normally.